A Comparative Study Between The Papua Contextual Textbook (BPKP) and The Government Published - Felix Degei (CV. Syntax Corporation Indonesia, 2023)
This paper is a study of two mathematical resources in the Indonesian primary education system. It is an empirical study that will compare the two booklets in the West Papua context. This paper will concentrate on 4 aspects of a contextual analysis framework used the Trends in International Mathematics and Science Study (TIMSS). The 4 aspects used in this study are structure, content, expectation and language. In 2013, Wamena Christian Foundation School (WCFS) published the Papua Contextual Textbooks: Buku Paket Kontekstual Papua (BPKP). These textbooks consisted of two subjects Mathematics and Bahasa Indonesia for Grade 1, 2 and 3 at the Primary Schools. This research examines the resource “Buku Paket Kontekstual Papua” (BPKP) which was designed by Wamena Christian Foundation School (WCFS) and the other resource “Matematika Untuk SD/MI Kelas 1” (MTG1_DH) which is the government issues resource designed by Djaelani and Haryono in 2008. The purpose of these textbooks is to uplift the education outcome from Indigenous Papuans in literacy and numeracy. After many good results from testing the Governor of West Papua and The Head of Education and Cultural Department ordered all school to utilise the BPKP textbook for the delivery of maths instruction. This paper will examine the difference later in the paper. What also will be examined is why this was so? The Governor of West Papua and the Head of Education and Cultural Department ordered the usage of BPKP resource without any empirical evidence to support him excepting the testing results. In using the textbook analysis process the research was able to identify significant differences in all areas of the textbook analysis. Through this process, the research will TIMSS definition of what a textbook analysis should consist of TIMSS identify 4 areas that make a good textbook analysis. The structure requires you to incorporate reference, substitution, ellipsis, conjunction and lexical when examining books. Content has 4 factors that define an analysis. These are motivation, comprehension cues, technical aids and philosophical position. Expectation requires empathy and philosophy. Language examines the narration and description aspect of a text. This analytical research paper will highlight the significant difference between the two resources and the effect it has on the West Papuan learners of Mathematics in the Primary School grades of 1, 2 & 3.